Systematic Identification of Endogenous Retroviral Protein-Coding Genes Expressed in Canine Oral Malignant Melanoma - Kitao, Koichi; Sumiyoshi, Aoi; Nakagawa, So; Matsumoto, Yuki; Mizuno, Takuya; Miyazawa, Takayuki (Frontiers in Virology, 2021)
Endogenous retroviruses (ERVs) are remnants of ancestral retroviruses that infected host germ cells in the past. Most ERVs are thought to be non-functional elements, but some ERVs retain open reading frames (ORFs) capable of expressing proteins. The proteins encoded by ERV-ORFs have potential roles in oncogenesis; however, studies on mammals other than humans and mice are limited. Here, we identified ERV-derived genes expressed in canine oral malignant melanoma (OMM). We identified 11 ERV-derived genes in our OMM samples. Differential expression gene analysis revealed that four ERV-derived genes (PEG10, LOC102155597, and two newly identified genes) were upregulated in OMM compared to healthy tissues. PEG10 is a conserved long terminal repeat (LTR)-type retrotransposon-derived gene among mammals and in involved in human cancers. LOC102155597 is a retroviral env gene conserved in Carnivora. This Env protein harbors an immunosuppressive domain, implying the potential adverse effects on the immune system. While the production of viral particles from ERVs has been reported in human and mouse melanoma, we found no ERV-derived genes having the potential to produce viral particles. These results provide insights into the different and conserved features of ERV-derived genes in mammalian melanoma.